DLR’s Antarctic Greenhouse Module Project - Schubert, D.; Poulet, L.; Zabel, P.; Zeidler, Conrad (2013)
Humanity’s plans to further explore the solar system requires the development of bio-regenerative life support systems (BLSS), fully incorporated into the habitat infrastructure. A Greenhouse Module (GHM) would contribute to food production, CO2 reduction, O2 production, water recycling and waste management. It is essential to test these GHM technologies in a similar environment to space and with relevant mass flows in order to increase their Technology Readiness Level. The German Aerospace Center (DLR) is planning to design and operate a GHM test facility at an analogue test site. Therefore, the Antarctic Neumayer Station III of the German Alfred Wegener Institute (AWI) has been identified as an ideal testing ground.